The CMAM facility for proton-therapy pre-clinical studies: biomaterial irradiation experiments. (1st March 2023) - Viñals, S.; García, G.; Magro, R.; Manso, M.
Abstract: CMAM is a multidisciplinary-oriented scientific facility based on the operation of a 5 MV tandem ion accelerator and a suite of six beamlines, along with complementary infrastructures and scientific tools. This work describes CMAM, highlighting some of the present and future collaborations and standing out radiobiology (in particular Proton-therapy) as a strategic research line with high societal relevance. Proton-therapy has been, since the last thirty years, an alternative to conventional radio-treatment to heal or control radio-resistant cancers or tumours near sensitive organs such as spinal cord or brain tumours. The research in this field has a multidisciplinary approach since biologist, chemists and physicist must work together to detangle the different effects that are produced by the radiation. Flexible facilities such as CMAM may play a very relevant role in order to develop further basic knowledge and as a training field for students to this type of investigation. As an example of this, a preliminary radiobiology experiment is briefly described, in which a non-alive material with a similar composition than a cell culture was used to see the effects of the radiation and it was developed the basic methodologies for dose delivery and proton range control. The experiment was also used as a training practice for students in the framework of the INFIERI school conducted at Universidad Autónoma de Madrid in Summer 2021.